Antimicrobial Characterization of Erythorbyl Laurate for Practical Applications in Food and Cosmetics. (19th February 2020) - Kim, Jin-Woo; Yu, Hyunjong; Park, Kyung-Min; Chang, Pahn-Shick
Abstract : In this study, antimicrobial spectrum of erythorbyl laurate (EL) against bacteria and fungi, leading to food-borne and infectious skin diseases, was evaluated for its practical applications in food and cosmetics. Furthermore, the influences of environmental factors including pH, oxidative stress, and dispersion medium on antimicrobial activity of EL were investigated. The three Gram-positive bacteria and the three molds were susceptible to 3.0 mM EL, while the yeast was susceptible to 6.0 mM EL. It was demonstrated EL retained antibacterial activity against Staphylococcus aureus after being oxidized while the antibacterial activity against the three Gram-positive bacteria including S. aureus, Bacillus cereus, and Listeria monocytogenes was significantly enhanced as decrease of pH from 7.0 to 5.0. Moreover, EL exhibited bactericidal effects against both Gram-positive and Gram-negative bacteria in an oil-in-water emulsion. Treatment of 5.0 mM EL for 4 h reduced 5.29 ± 0.24, 6.01 ± 0.18, 5.95 ± 0.13, and 6.24 ± 0.30 log CFU/mL against S. aureus, L. monocytogenes, Pseudomonas aeruginosa, and Escherichia coli, respectively. In a multipassage resistance selection study, it was observed minimum inhibitory concentrations of EL against S. aureus were not increased over 20 passages, indicating EL might not develop drug resistance of bacteria. This study suggests EL has a potential to be applied as the multifunctional additive in food and cosmetics.